Evaluation of Cardiovascular Involvement and Cytokine Levels in Patients with Mucopolysaccharidosis - Ebru Canda; Melis Köse; Mehtap Kağnıcı; Meral Dondurmacı; Sema Kalkan Uçar; Eser Sözmen; Reşit Ertürk Levent; Mahmut Çöker (Galenos Yayinevi, 2019)
Aim:Cardiovascular involvement is common in patients with mucopolysaccharidoses (MPS). In this study, we investigated the effects of the markers involved in vascular endothelial injury pathogenesis [transforming growth factor β- (TGF-β)], interleukin-6 (IL-6), IL-10, high sensitive-C reactive protein (hs-CRP), vascular endothelial growth factor (VEGF), N-terminal pro-Natriuretic peptide (NT-proBNP) and the clinical, laboratory and echocardiographic findings of the patients.Materials and Methods:A total of 37 patients (5 MPS I, 4 MPS II, 2 MPS IIIa, 4 MPS IIIb, 14 MPS IVa, 8 MPS VI) and 32 controls with similar age and sex were included in the study.Results:Corneal clouding was seen in 29 (78%) patients. There were 23 (62%) patients with organomegaly, and 28 (75%) patients with hearing loss. When the groups were compared in terms of NT-proBNP, hs-CRP, TGF-β, IL-6, IL-10 and VEGF levels, there was a statistically significant increase in the patient group for NT-proBNP and VEGF (p=0.04, p=0.03, respectively). The carotid intima media thickness was statistically significantly higher in the patient group (p<0.001). The left ventricular diastolic diameter was significantly higher in the patient group (p=0.009), intraventricular septum thickness was significantly higher in the patient group (p<0.001). The E/A ratio was significantly lower in the patient group (p<0.001).Conclusion:Cardiac involvement in MPS patients is a major cause of mortality and morbidity. It is thought that cytokines, proinflammatory markers are elevated in patients with vascular damage like other lysosomal diseases. There is a need for further studies to determine biomarkers for vascular involvement.